The Relationship of Students' Initial Ability and Emotional Intelligence with Learning Outcomes - Salam, Agus; Irwan (Al-Hayat: Journal of Islamic Education, 2025)
This study aims to determine the relationship between initial abilities and emotional intelligence with student learning outcomes. This study uses a quantitative approach with a survey method and correlational analysis techniques. The study population consisted of 120 PGMI students of the 2022/2023 intake. The study population of students of the 2022/2023 intake was 120 students. The results of this study were processed using regression analysis techniques of simple correlation, partial correlation, regression, and multiple correlation. The study found that there was a positive and significant correlation between (a) Initial abilities (X1) and learning outcomes (Y) with Ŷ = 7.93 + 1.938 X1 and ry1 = 0.798; (b) emotional intelligence (X2) and learning outcomes (Y) with Ŷ = 18.94 + 0.186X2 and ry2 = 0.90. So it is known that there is a positive relationship between initial ability (X1) and emotional intelligence (X2) with student learning outcomes (Y) with Ŷ = 21.1 + 0.103 X1, +0.33X2 and a correlation coefficient of ry12 = 0.87. This study is limited to PGMI students of the 2022/2023 intake at one institution with a correlational design, so it cannot be generalized and does not show a causal relationship. In addition, other factors such as learning motivation and environment were not analyzed. This study combines initial ability and emotional intelligence as predictors of learning outcomes in the PGMI context, resulting in a multiple regression model with a strong correlation that can be used as a basis for developing educational strategies.